FAKTOR-FAKTOR PENYEBAB TERJADINYA HIPERTENSI DI RUMAH SAKIT PTPN BANGKATAN BINJAI TAHUN 2017 - Hasan Basri Nasution (Jurnal Riset Hesti Medan, 2017)
Hypertension is a condition in which a person who experiences an increase in blood pressure above normal is indicated by a systolic number (upper part) and a lower diastolic number on a blood pressure examination using a measuring device (sphygmomanometer). The relative factors of hypertension depend on the number and severity of the risk factors that can be controlled and the factors that cannot be controlled, which is the reason the researchers made a study with the names of the causes of hypertension in PT Departure II Bangkat Binjai Hospital. This study aims to determine the causes of hypertension in PTPN Bangkatan Binjai Hospital. Data analysis uses variate analysis (descriptive) using the Guttman scale measurement scale. For the problem of the characteristics of respondents based on occupation, the majority of respondents have jobs of PTPN employees totaling 9 people (30%), based on offspring who are not dominant so influenced by the number of 18 people (60%), based on age which shows the most age who suffer from hypertension aged 51-55 years, amounting to 11 people (37%), and based on sex, the men suffered the most hypertension, amounting to 16 people (53%), based on the highest level of education, namely high school education as many as 13 people (43% ), and based on salt intake there are 17 people (57%), based on smoking habits the same results as those who do not smoke. So, it can be concluded that there are factors that cause hypertension. So it is expected for respondents to improve their lifestyle and avoid the trigger factors of hypotension, and it is expected that nurses in PT Bangkat Binjai Hospital also provide health promotion to patients on ways to avoid hypertension, and it is hoped that later writers can use this scientific paper as a guide and reference in making scientific papers.Keywords: Hypertension, Dystolic, Systolic